Glossário bilíngue: registro dos sinais comuns dos órgãos e locais públicos da cidade de Manaus em Libras - Brito, Eline Alves (Brasil, 2025)
This research was motivated by the experience found during participation in an internship in translation and interpretation at the Manaus City Council. The research aims to develop the sharing a glossary in Libras of toponyms from the city of ManausAm, in order to contribute to the teaching and learning of deaf people, serving as support material for interpreters and professionals in the field. The basis of the theoretical foundation was made up of related studies; Lexicography (Isquerdo; Krieger, 2004); Lexicon (Biderman, 2002); Lexicology (Guerra; Andrade, 2012); Terminology (Isquerdo; Krieger, 2004); Toponymy (Souza-Júnior, 2012). This project aims to address the needs of the deaf community in Manaus and the state of Amazonas. Initially, it will be made avaliable on a YouTube channel, with the potential to reach a national audience. The content will be accesible to professionals in the field, including translators, interpreters of Brazilian Sign Language (LSB), deaf and hearing academics, and the general public. To present the results, initially 20 terms were chosen, but only 11 were selected for this work. This work was relevant to the Deaf community of Manaus and Amazonas. It can contribute throughout Brazil, as it will be published on the YouTube channel for access by professionals in the field, translators, Libras interpreters (TILSP), Deaf and Hearing students and teachers, in short, everyone who needs these signs.